2022
DOI: 10.3390/antiox11051020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant Capacity and Gut Microbiota Modulatory Effects of Different Kinds of Berries

Abstract: Berries are fairly favored by consumers. Phenolic compounds are the major phytochemicals in berries, among which anthocyanins are one of the most studied. Phenolic compounds are reported to have prebiotic-like effects. In the present study, we identified the anthocyanin profiles, evaluated and compared the antioxidant capacities and gut microbiota modulatory effects of nine common berries, namely blackberry, black goji berry, blueberry, mulberry, red Chinese bayberry, raspberry, red goji berry, strawberry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…This systematic review and meta-analysis demonstrated that dietary anthocyanin supplementation profoundly improves rodent models' gut health biomarkers (Fir/Bac and SCFAs). This finding was supported by studies carried out after cut off time limit of this studies 77 81 .…”
Section: Discussionsupporting
confidence: 84%
“…This systematic review and meta-analysis demonstrated that dietary anthocyanin supplementation profoundly improves rodent models' gut health biomarkers (Fir/Bac and SCFAs). This finding was supported by studies carried out after cut off time limit of this studies 77 81 .…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, one study [ n = 1; 6.25%] assessed the colonic antioxidant status through levels of T‐AOC, glutathione (GSH), T‐SOD, CAT, glutathione peroxidase (GSH‐PX), and MDA. [ 25 ] This study observed an increase in the levels of SOD and AOC in the colon compared with the control group following the intake of blueberry extract.…”
Section: Resultsmentioning
confidence: 83%
“…The studies included in this article [ n = 16] were performed in four different countries that include China [ n = 7], [ 19–25 ] USA [ n = 4], [ 16,26–28 ] Canada [ n = 3], [ 29–31 ] Ukraine [ n = 1], [ 32 ] and Sweden [ n = 1]. [ 33 ] Regarding the animal model used in the studies, 11 of them were performed with mice [ 19–23,25,28–31,33 ] and five were performed with rats. [ 16,24,26,27,32 ] Most studies used male animals [ n = 14] [ 16,19–33 ] and two used both male and female animals.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that, polyphenols and their metabolites, such us simple phenolic acids and phenolic acids conjugated with short chain fatty acids jointly modulate the microbial community. The administration of polyphenols may increase the levels of short chain fatty acids by changing the composition of the gut microbiota, promoting the short chain fatty acids producing bacteria [23,24]. Short-chain fatty acids, such as butyrate, propionate, and acetate are produced via fermentation of indigestible carbohydrates by intestinal anaerobic commensal bacteria, including clostridia, lactobacilli and bi dobacteria species [25].…”
Section: Discussionmentioning
confidence: 99%